Hubungan antara Problem Focused Coping dan Resiliensi Warga Surabaya selama New Normal - Sayidah Aulia Ul Haque; Eko April Ariyanto; Ricky Alejandro Martin; Muchammad Rizal; Amalia Eka Kurnia Sari (Syntax Literate, 2022)
The current COVID-19 pandemic has entered a new era, namely the new normal period or the era of adapting to new habits, in this new normal period, each individual is expected to be able to carry out a series of new habits. The condition in which a person is asked to immediately adapt to new rules and conditions while surviving the impact of COVID-19 of course has the potential to cause psychological pressure on someone, including the residents of Surabaya. As a result, in this case it is important for residents to have and develop resilience or psychological resilience and coping to resolve the discomfort that arises. In this case the coping that wants to be studied is problem focus coping where the coping is related to how a person's real action is to reduce the feeling of comfort from existing psychological pressure. This research was conducted to determine the relationship between resilience and problem focused coping of Surabaya residents in the new normal period. The research method used is a quantitative method using a simple linear regression test with the help of SPSS 21. The data collection tool uses a resilience scale and a problem focused coping scale. The sample in this study were residents of Surabaya, amounting to 400 people and using a random sampling technique. From the test results obtained the magnitude of the correlation 0.037 with a significance of 0.230, the significance value (p) > 0.05. Thus, the results of the study indicate that there is no correlation between problem focused coping and the resilience of Surabaya residents during the new normal period. Keywords: Resilience; Problem Focused Coping; Covid-19; New Normal